Cultural Representation to EFL according to English Textbooks for Twelfth Grades in Indonesia - Iin Inayah; Yeni Sriyeni (English Teaching and Linguistics Journal (ETLiJ), 2022)
The study aims to examine cultural content in the textbooks for Senior High School grades 12th and how represents the culture in textbooks through the material to be studied in the textbooks. This research applied a descriptive qualitative method, data obtained from English textbooks for 12th grades from Indonesia which are analyzed by grouping cultural elements. To collect the data, this research applies document review. The finding shows there are three elements of culture in this textbook. 1. Practice 2. Person 3. Product. These English textbooks introduce many various cultures around the world not only England or American culture but also, a lot of other countries including Indonesian culture.